Breast Lipofilling Does Not Pose Evidence of Chronic Inflammation in Rats. (28th September 2018) - Claro, Francisco; Morari, Joseane; Moreira, Luciana R; Sarian, Luis O Z; Velloso, Licio A
Abstract: Background: Laboratory reports on adipose tissue suggest that fat grafting to the breast may pose an oncologic risk. One possible reason for this is the theoretic chronic inflammation due to adipokynes released by grafted white adipose tissue (WAT). Objectives: The aim of this study was to analyze inflammatory activity in lipofilled breast through the use of proinflammatory markers. Methods: Fifty-four paired-breasts of female rats were divided into 4 groups: control, sham, and breasts grafted with either autologous subcutaneous (SC) WAT or autologous omentum (OM). The WAT was prepared through centrifugation, and the grafting was performed with the use of 0.9-mm blunt-tip cannula. The rats were killed 8 weeks postoperatively, and their breasts were harvested for immunohistochemical staining for CD68 -expressing macrophages, gene expression (real-time PCR) for monocyte chemoattractant protein 1 ( MCP-1 ), F4/80, Cox-2, and IL-6 . Results: The weights of the rats that underwent a procedure differed from those of the unmanipulated control group ( P < 0.01). The macrophage counts of CD68 differed only between breasts lipofilled with OM and control ( P < 0.01). MCP-1, F4/80, and Cox-2 were similarly expressed among the groups ( P = 0.422, P = 0.143, and P = 0.209, respectively). The expression of IL-6 differed between breast samples grafted with SC and OM WAT ( P = 0.015), but not between samples of control and OM ( P = 0.752), and control and SC ( P = 0.056). Conclusions: No inflammation activity was identified in the microenvironment of lipofilled breasts, indicating that chronic inflammation does not seem to be triggered by the breast lipofilling procedure.